2020
DOI: 10.1093/mnras/staa1036
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the engines of fast radio bursts

Abstract: We model the sample of fast radio bursts (FRB), including the newly discovered CHIME repeaters, using the decelerating synchrotron blast wave model of Metzger, Margalit & Sironi (2019), which built on earlier work by Lyubarsky (2014), Beloborodov (2017). This model postulates that FRBs are precursor radiation from ultra-relativistic magnetized shocks generated as flare ejecta from a central engine collides with an effectively stationary external medium. Downward drifting of the burst frequency structure natura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 114 publications
(230 reference statements)
4
112
0
Order By: Relevance
“…Indeed, some FRB sub-pulses exhibit downward frequency drifts (Gajjar et al 2018;Hessels et al 2019;CHIME/FRB Collaboration et al 2019a), in which the peak frequency of the spectrum decreases over time. Within the framework of the baryonic shock model for FRBs, these drifts can be directly related to the external density profile (Margalit et al 2020b). That being said, the recently discovered FRB 200428, exhibits a significant lack of emission at frequencies below ∼ 550 MHz for the second pulse (The CHIME/FRB Collaboration et al 2020), and a lack of frequency down-drift, which are not expected according to the shock model.…”
Section: Physical Processes and Parameters That Control Light-curve Vmentioning
confidence: 97%
“…Indeed, some FRB sub-pulses exhibit downward frequency drifts (Gajjar et al 2018;Hessels et al 2019;CHIME/FRB Collaboration et al 2019a), in which the peak frequency of the spectrum decreases over time. Within the framework of the baryonic shock model for FRBs, these drifts can be directly related to the external density profile (Margalit et al 2020b). That being said, the recently discovered FRB 200428, exhibits a significant lack of emission at frequencies below ∼ 550 MHz for the second pulse (The CHIME/FRB Collaboration et al 2020), and a lack of frequency down-drift, which are not expected according to the shock model.…”
Section: Physical Processes and Parameters That Control Light-curve Vmentioning
confidence: 97%
“…The fact that the second radio burst detected by CHIME appears to have a rising spectrum is also in tension with this model (since n~10 MHz pk , as discussed above), although scintillation may affect the observed spectrum (Simard & Ravi 2020). (Metzger et al 2019;Margalit et al 2020) In this version of the synchrotron maser model, first proposed by Beloborodov (2017), the ultrarelativistic head of the magnetar flare collides not with the magnetar wind nebula but rather with matter ejected from a recent, earlier flare. Motivated by the inference from the radio afterglow of the 2004 giant flare from SGR 1806-20 of a slow ejecta shell generated by the burst (Gelfand et al 2005;Granot et al 2006), Metzger et al (2019) considered the upstream medium to be a subrelativistic baryon-loaded shell with an electron-ion composition.…”
Section: Magnetar Wind Nebula (Lyubarsky 2014)mentioning
confidence: 99%
“…x -f 10 10 2 3 (for moderate magnetization; Plotnikov & Sironi 2019) and a further reduction by a factor of~-10 2 due to the effects of induced Compton scattering suppressing the low-frequency portion of the maser's intrinsic SED (see Metzger et al 2019, their Section 3.2). 18 Following the methodology of Margalit et al (2020), we can use the energy, frequency, and duration of the observed radio burst to derive the intrinsic parameters of the flare demanded by the synchrotron maser model. Adopting the observed quantities from Section 2, we find that the energy of the relativistic flare, E ;…”
Section: Baryonic Shellmentioning
confidence: 99%
See 1 more Smart Citation
“…5.1.1. Metzger et al (2019) ModelSynchrotron masers have been widely discussed as an astrophysical coherent emission process (e.g.,Hoshino & Arons 1991;Long & Pe'er 2018), and one common variation is coherent emission from synchrotron masers produced by ultrarelativistic shock in magnetized plasmas (e.g.,Langdon et al 1988;Lyubarsky 2014;Beloborodov 2017Beloborodov , 2019Margalit et al 2020;Metzger et al 2019).Metzger et al …”
mentioning
confidence: 99%